Main Problems of Supply of Goods and Material Resources in Economic Owners - M.I. Xayitboev (International Journal on Economics, Finance and Sustainable Development, 2022)
This article describes the nature of inventories, their role in the activities of business entities. The article develops the main stages of inventory management policy. As a result of the research, the main problems related to the supply of inventories were clarified and directions for their elimination were recommended.